Aligning Indonesia's economic goals with SDGS: Strengthening Qur'anic principles in Islamic finance - Azwar, Azwar; Abur Hamdi Usman (Jurnal Ekonomi & Keuangan Islam, 2025)
Purpose – This research examines the relationship between Islamic bank financing aligned with the Sustainable Development Goals (SDGs) and economic growth, incorporating Qur'anic principles in Islamic finance.Methodology – Quarterly time-series data from Q1 2014 to Q1 2022 were analyzed using the cointegration and ARDL approaches. Data sources include the PSIFIs for Islamic Banks (IFSB Database), Indonesia's GDP (BPS), and the Financial Services Authority (OJK).Findings – Long-term analysis reveals that Islamic financing in SDG sectors such as SDG1 (No Poverty), SDG2 (Zero Hunger), SDG3 (Good Health and Well-being), SDG4 (Quality Education), and SDG11 (Sustainable Cities and Communities) positively correlate with economic growth, while SDG8 (Decent Work and Economic Growth) shows an inverse relationship. In the short term, financing in SDG2, SDG3, SDG8, and SDG9 (Industry, Innovation, and Infrastructure) positively impacts economic growth, whereas SDG6 (Clean Water and Sanitation) exhibits a negative association. These findings highlight Islamic finance's potential to address socio-economic challenges rooted in Qur'anic values, such as Surah al-Nisā’ [4]: 29 and al-Baqarah [2]: 261.Implications – Policymakers are encouraged to promote Islamic microfinance for SMEs and invest in rural sanitation infrastructure (SDG6). Furthermore, financing renewable energy projects (SDG7) aligns with sustainable development goals.Originality – This study bridges Islamic finance and sustainable development by integrating a Qur'anic perspective into the SDG framework, offering insights into leveraging Islamic finance to achieve sustainability and economic growth, while adhering to Islamic ethical principles.